SARS-CoV-2 RNA viability on high-touch surfaces and evaluation of a continuous-flow ozonation treatment - Diella, G.; Caggiano, G.; Apollonio, F.; Triggiano, F.; Stefanizzi, P.; Fasano, F.; Pace, L.; Marcotrigiano, V.; Sorrenti, D. P.; Galante, D.; Montagna, M. T. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The COVID-19 emergency has highlighted the importance of prevention systems and environmental microbiological monitoring as fundamental elements in the response to epidemics and other such threats to individual and collective health. The use of automated “No-touch” room disinfection systems eliminates or reduces the dependence on operators, thus allowing an improvement in the effectiveness of terminal disinfection. Study design. In the present study, we focused on possible SARS-CoV-2 contamination of surfaces of commercial services, and the effectiveness of ozone treatment on the virus. Methods. Analyses were conducted on 4-7 October and 27-30 December 2021 in four supermarkets in an Apulian city; supermarkets A and B were equipped with an ozonisation system, while C and D were without any environmental remediation. Results. SARS-CoV-2 RNA was detected by real-time RT-PCR only in December, in 6% of the surfaces tested, and all examined samples were found to be negative after viral culture, since no cytopathic effect was observed. A statistically significant difference emerged from the comparison of October vs. December (p = 0.0289), but no statistically significant difference (p = 0.6777) emerged from the comparison between supermarkets with and without the ozonisation system. Conclusions. Although no important changes were observed by treating the environments with ozonisation systems, further studies are needed to validate the effectiveness of environmental treatments with airborne disinfectants.